Gelagat Pencarian Maklumat di Jabatan Perkhidmatan Penerangan dan Jabatan Penyiaran Malaysia - Ibrahim, Ali (1998)
This study investigated the information seeking behavior of communicators from Department of Information (DOI) and Department of Broadcasting (DOB). The objectives of this study were to determine the level of information seeking among communicators at DOI and DOB, to determine the relationship between variables of information adequacy, knowledge importance, information source accessibility, and information source usefulness with information seeking, to compare communicators’ information seeking behavior between respondent in DOI and DOE, and lastly to determine the best predictor variables of information seeking. Respondents were 127 employees (Assistant information Officer Grade S7 and Producers Grade 67) in Perks, Kedah, Penang and Perak from both departments. Data were obtained through self-administered questionnaires. Descriptive and inferential statistics were used to analyze data. Twelve information potential sources of which communicators could obtain information about organization, task, and audience were included. These were further combined into three indices of information sources: interpersonal source (supervisor, co-worker, course/briefing, officer outside the department, and audience), written source (notice board, departmental print sources, printed sources (newspaper and magazines), and electronic sources (radio, television, and Internet). Findings revealed that 1) the level of information seeking among the respondents were relatively high for written sources, and were moderates for interpersonal and electronics sources, 2) information seeking from interpersonal and electronics sources among communicators’ of DOD was higher than DOI, 3) there were no significant difference between gender and job tenure with information seeking but age were negatively related, and 4) there were positively significant relationship between information adequacy, knowledge importance, information source accessibility, and information sources usefulness with communicators’ information seeking. The major finding of this study revealed that perceived information source accessibiliiy and perceived information source usefulness were the best predictors of communicators’ information seeking behavior. It was recommended that both departments need to increase their effort in facilitating information source accessibility and the usefulness (quality) of information sources in order to promote information seeking among the communicators.